Exploring Peer Support as a Strategy to Reduce Stigma among PLHIV - Adistha Eka Noveyani; Triska Dwi Cahyani; Khoirunnisa Yunita; Anis Latifah; Mochammad Farhan Maulana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Background: Efforts to reduce stigma and discrimination are important factors in efforts to reduce HIV cases, especially mortality, and increase the treatment rate for PLHIV. Objective: This study aimed to obtain evidence of efforts to reduce stigma and discrimination in healthcare facilities Methods: This research is a Mix Methods study. The population was HIV/AIDS patients in the Puger and Kencong areas. The sampling technique was purposive sampling. The variables included the level of discrimination, medication adherence, and stigma reduction strategies. Quantitative data were analyzed descriptively, and qualitative data were analyzed by content analysis. Results: the level of discrimination felt by PLHIV is 100% which is low. While the level of adherence to taking medication for the majority of PLHIV is classified as high, namely 69.7%. The success in reducing stigma and discrimination in health services is influenced by factors that accompany PLHIV and health workers, where assistants always help PLHIV in carrying out examinations, and officers are also friendly to PLHIV, so this is what can make discrimination experienced by PLHIV low. Conclusion: Success in reducing stigma and discrimination in healthcare facilities was proven by high adherence to taking medication, and the low level of discrimination experienced by PLHIV.Keywords:  PLHIV, HIV/AIDS, discrimination, stigma, strategy